A Critical Examination of My Qualitative Research Efforts in Turkey - Yıldız Uzuner (Anı Publishing, 2015)
Today, it is known and widely accepted that researchers must know the research paradigms and develop skills and non-dogmatic attitudes for conducting and evaluating studies in any methodology. Quantitative research methodology is more common while qualitative research is relatively new in Turkey. Researchers who have not developed sufficient knowledge and experiences in qualitative study would create non-evidence based and non-ethical research projects. This creates threats to the research community. In order to improve and be competent in any methodology, it is important to review and critically analyze the completed dissertations, thesis and the journal articles emerged from those research efforts. In this effort self-reflection of one's own research effort is essential. In this paper as an experienced researcher the author shares her experiences in supervising theses and dissertations and conducting her own research projects in qualitative research methodology in the last 20 years in Turkey. In the light of the literature considering various aspects she discusses advantages and disadvantages conducting qualitative studies in Turkey. Considering the disadvantages, the author came up with the idea of keeping thinking positively, acting modestly, being patient, learning how to deal with the authority, learning how to deal with the exploiters, working hard, never giving up, focusing on the target, being assertive when necessary, and so keeping going in the scientific way.